"Drama" in Interpersonal Conflict and Interactions Among Emerging Adults: A Qualitative Focus Group Study. Issue 2 (April 2020) - Smith, Alexandra C. G.; Fritz, Patti A. Timmons; Daskaluk, Samantha
Drama is a term used in popular culture to refer to interpersonal conflict that arises when individuals overreact to events and are overly emotional. The current study investigated emerging adults' perspectives of drama, the context in which it occurs, and how drama relates to similar social interactions such as conflict, bullying, and relational aggression. University students ( N = 53; 18–25 years old) participated in eight same-sex focus groups. Using thematic analysis, seven main themes were found, suggesting that "drama" (a) refers to a wide range of situations, (b) is often associated with negative social interactions, and (c) harm and consequences, (d) is generally perceived as unnecessary, (e) exaggerated, and (f) involving females, and (g) frequently offers a learning experience. Findings suggest that future research should continue to explore drama as its own construct and that drama should be addressed more formally given how youth may be impacted by such incidents.